DOI: 10.11606/t.11.2013.tde-06092013-101823
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência de equações empíricas utilizadas para determinar lâmina de lixiviação de sais e modelagem da distribuição do sódio no solo

Abstract: AGRADECIMENTOS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
1
1
1
Order By: Relevance
“…The results found in this study are different from the values obtained by Franco [24], who used the equations of Volobuvev, Cordeiro, Jury, Hoffman, and Reeve in a study with the same soil and two levels of salinity. The author suggested that the best equation was that of Cordeiro for calculation of the salt leaching depth in soils salinized with sodium chloride.…”
Section: Performance Of the Equations For Soil Salinity Prediction Incontrasting
confidence: 99%
See 1 more Smart Citation
“…The results found in this study are different from the values obtained by Franco [24], who used the equations of Volobuvev, Cordeiro, Jury, Hoffman, and Reeve in a study with the same soil and two levels of salinity. The author suggested that the best equation was that of Cordeiro for calculation of the salt leaching depth in soils salinized with sodium chloride.…”
Section: Performance Of the Equations For Soil Salinity Prediction Incontrasting
confidence: 99%
“…Franco [24] also pointed out that his results differ from some papers reviewed by him, which were highly variable due to the soil diversity and the conditions under which the studies were carried out. Thus, the results obtained by the reclamation equations may depend on soil physical-chemical factors, on the chemical composition of the washing water or on factors inherent to the method used.…”
Section: Performance Of the Equations For Soil Salinity Prediction Inmentioning
confidence: 78%
“…Os valores do coeficiente de determinação, do coeficiente de correlação linear de Pearson, do índice de concordância de Willmott, do índice de desempenho de Tabela 9 -Valores dos coeficientes de determinação (R 2 ), de correlação linear de Pearson (r), do índice de concordância de Willmott (w), do índice de desempenho de Camargo Sentelhas (c), do erro-padrão da estimativa (EEP) e da raiz do quadrado médio do erro (RQME) obtidos nas correlações entre os valores de CE estimados e CE medidos no sistema de Ainda Franco (2013), ressalta que os valores obtidos pelas equações diferem de alguns trabalhos apresentados na literatura, e que esses são bastantes variáveis, o que pode estar relacionado com a diversidade de solos e das condições em que foram realizados os estudos.…”
Section: Estatísticas Clássicas Para a Performance Das Equações Empírunclassified